The Development of Kelab Golf Batu Pahat Online Shopping - MUHAMMAD AMIR DANIEL BIN SUHAIMI,; Ruhaya Ab. Aziz, (Applied Information Technology And Computer Science, 2025)
Kelab Golf Batu Pahat Online Shopping, a web-based sales and stock management system were proposed for customers to purchase their golf equipment. The prototyping model is chosen in this project because user involvement is critical and effective for this project with a user-centric focus where visual representation of the system plays a crucial role in its overall success. Through the system, customers can make a golf equipment purchase online while the staff can manage their stocks and orders efficiently. Visual Studio Code, MySQL AND XAMPP are the software used in this project. The development of this system will provide the customers a more convenient system to purchase golf equipment and staff to have a better stock management system.